Berlin 1945. The image of the defeated city in the light of Allied memoirs and reports - Nikel, Joanna (City and War, 2021)
The aim of this article is to present an image of the fallen German capital, as seen through the eyes of Soviet and American political officers, responsible for rebuilding German life in the sectors of Berlin they occupied. The image of Berlin presented in this article is a picture of the city as seen primarily through the eyes of Soviet officers: Alexander Dymschitz, a literary scholar and cultural editorial staff member at the Tägliche Rundschau newspaper published by the Russians as early as 15 May, Sergei Tjulpanov – head of the Propaganda Board of the Soviet Military Administration in Germany (SMAD), and Grigory Weiss, an officer in the Cultural Department of SMAD. The narrative is supplemented by testimonies of Western Allies – memoirs of General Frank L. Howley and reports of American political officers, a selection of which was presented in 1979 by historian Brewster S. Chamberlin. The aim of the narrative based on the above-mentioned sources will be to show Berlin through the eyes of the Allies, which will also serve as a pretext for asking the question about the so-called “Americanisation” and “Sovietisation” of German society immediately after the end of the Second World War.